Model Pengembangan Kreativitas melalui Permainan Konstruktif dalam Proses Pendidikan Anak Usia Dini - Masnipal Masnipal (Pusat Penerbitan Universitas (P2U) Unisba, 2016)
This research is aimed at developing a creativity development model through constructive play using building blocks. By testing the hypothesis using t test, this research results in the Creativity Development Model through Constructive Play. Model proves to be effective in increasing the creative thinking ability of pre-school children. The research findings imply that provide empiric information about constructive play as a means of developing the creativity in pre-school children; can give empiric information about constructive play as tool for development of self in pre-school children; can be used to help them in developing pre-school children’s creativity, especially through constructive play activities.